TEACHING FOREIGN LANGUAGES IN AGGREGATED SMALL ACADEMIC GROUPS OF DIFFERENT SPECIALITIES AS A PART OF STRUCTURAL CONSOLIDATION WITHIN UKRAINIAN EDUCATIONAL SYSTEM - Kolesnyk, Alina; Arkhypova, Viktoriia; Manuyenkova, Olena; Podvorna, Liudmyla; Muraviova, Olena (European Science, 2024)
Education is a phenomenon that shapes the value orientation of students and a key resource in such areas as innovative economy, social cohesion and the development of social culture.If we talk about the prospects for Ukrainian universities in the next 5-